2012
DOI: 10.1590/s0103-21002012000500013
|View full text |Cite
|
Sign up to set email alerts
|

Clima de segurança do paciente: percepção dos profissionais de enfermagem

Abstract: Objective: To evaluate the perception of the safety climate of nursing professionals working in the medical and surgical clinics of a teaching hospital. Methods: A cross-sectional, descriptive study using a quantitative approach. We used the Safety Attitudes Questionnaire (SAQ) -Short A satisfação no trabalho foi demonstrada por todos os profissionais, com escores acima de 75, enquanto o domínio Percepção da Gerência apresentou valores mais baixos. Conclusão: A satisfação do profissional, o diálogo e o suporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
51

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(95 citation statements)
references
References 21 publications
(32 reference statements)
1
38
0
51
Order By: Relevance
“…This finding differs from those found in the literature, in which professionals with 21 years or more in the institution presented higher means. (14,27) This study showed a better perception among professionals who had worked less than six months in the institution, and this result relates to adaptation to the work environment, since staff positively perceived the organization. (24) Also, the divergence among professionals with different years of work time may be related to the new methods of qualification, selection, and evaluation of professionals when entering the job market.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…This finding differs from those found in the literature, in which professionals with 21 years or more in the institution presented higher means. (14,27) This study showed a better perception among professionals who had worked less than six months in the institution, and this result relates to adaptation to the work environment, since staff positively perceived the organization. (24) Also, the divergence among professionals with different years of work time may be related to the new methods of qualification, selection, and evaluation of professionals when entering the job market.…”
Section: Discussionmentioning
confidence: 73%
“…(10) Studies aimed at evaluating institutions in general are incipient. (11,12) To date, part of the scientific evidence on the subject evaluates specific units of an institution, such as: medical and surgical clinics, (13,14) bone marrow transplant unit, (15) surgery center, (16) surgical units , (17) outpatient unit, (18) emergency department, (19) intensive care unit. (20,21) This denotes knowledge gaps in the literature, which relate to patient safety from the perspective of the entire institution.…”
Section: Introductionmentioning
confidence: 99%
“…Essa percepção vinda do enfermeiro está relacionada com seu papel de liderança, visualizando a sobrecarga de trabalho, a fadiga e o estresse como fatores que podem influenciar nas atitudes que podem gerar o erro e comprometer a segurança do paciente (23) . O domínio Satisfação do trabalho foi o único que apresentou valor positivo para a cultura de segurança, resultado semelhante ao encontrado em outro estudo nacional (24) que também aponta a satisfação do profissional, o diálogo e o suporte à equipe por parte dos gestores como fatores essenciais para a segurança do paciente. A satisfação profissional contribui para a maior participação do profissional em seu ambiente de trabalho, tendo em vista que estando mais satisfeitas no trabalho, as pessoas passam a adotar atitudes mais positivas consigo e com os demais colaboradores (25) .…”
Section: Discussionunclassified
“…Os resultados encontrados nesta pesquisa demonstram fragilidade no clima de segurança da UE, assim como observado por Cauduro (2015) em pesquisa realizada em centros cirúrgicos brasileiros. De acordo com Carvalho (2011), para reduzir os eventos adversos é importante priorizar as questões de segurança por meio de ações preventivas e do 1 a 2 anos 5 (4) 9 (7,2) 14 (11,2) 3 a 4 anos 2 (1,6) 11 (8,8) 13 (10,4) 5 a 10 anos 10 (8) 10 (8) 20 (16) 11 a 20 anos 10 (8) 22 (17,6) 32 (25,6) 21 anos ou mais 12 (9,6) Resultado similar foi identificado em estudos realizados no Brasil e na Suíça, mas divergente de outros estudos internacionais que identificaram percepção desfavorável para o domínio "Satisfação no Trabalho" (CARVALHO; CASSIANI, 2012;CAUDURO et al, 2015;HUANG et al, 2007;RIGOBELLO et al, 2012;SEXTON et al, 2006;NORDEN-HAGG et al, 2010).…”
Section: Percepção Dos Participantes Quanto Ao Domínio "Clima De Seguunclassified
“…1 a 2 anos 5 (4) 9 (7,2) 14 (11,2) 3 a 4 anos 3 (2,4) 10 (8) 13 (10,4) 5 a 10 anos 9 (7,2) 11 (8,8) 20 (16) 11 a 20 anos 21 (16,8) 11 (8,8) 32 (25,6) 21 anos ou mais 16 (12,8) Itens do SAQ DT n (%) DP n (%) Neutro n (%) CP n (%) CT n (%) NA n (%) 20. Quando minha carga de trabalho é excessiva, meu desempenho é prejudicado 11 (8,8) 13 (10,4) 6 (4,8) (BOGNAR et al, 2008;CARVALHO;CASSIANI, 2012;CAUDURO et al, 2015;HOLDEN et al, 2010;RELIHAN et al, 2009;SEXTON et al, 2006 Para reduzir os níveis de estresse no contexto das urgências e emergências, recomenda-se equilibrar as escalas de trabalho com horas de descanso; desenvolver programas de bem-estar que apoiam um estilo de vida saudável; desenvolver e aplicar políticas de gerenciamento do estresse; além de melhorar as condições de trabalho e favorecer a igualdade de remuneração (BELLAGAMBA et al, 2015;MOSADEGHRAD, 2013;RICE et al, 2014 CASSIANI, 2012;CAUDURO et al, 2015;HUANG et al, 2007;KRISTENSEN et al, 2015;LEE et al, 2010;RAFTOPOULOS;PAVLAKIS, 2013;RELIHAN et al, 2009;RIGOBELLO et al, 2012;SEXTON et al, 2006;TAYLOR, 2008 (8,8) 33 (26,4) 34 (27,2) 13 (10,…”
Section: Percepção Dos Participantes Quanto Ao Domínio "Percepção Do unclassified